Kajian Konseptual Multiliterasi Berbasis Pendidikan Karakter untuk Meningkatkan Kemampuan Literasi Siswa Sekolah Dasar - muhilal, muhilal; Farikah; Mulyani, Mimi (Kajian Bahasa dan Sastra (KABASTRA), 2021)
This study aims to describe a multiliteracy study based on character education as an effort to increase students literacy skills. With the descriptive qualitative literature review method, it is hoped that in the implementation it is expected that multiliterate students will increase and instil strong character education. The data collection technique carried out by the author is through a literature review and field study evaluation of literacy activities in the implementation of Gerakan Magelang Membaca (GMM) in the Regional Education and Culture Office, Grabag District, Magelang Regency. This conceptual study is expected to be useful for teachers as education stakeholders and other parties relevant to this study. The results of the discussion with the analysis of the study that the concept of multiliteracy has been integrated into the education unit level curriculum (KTSP). in the practice of learning, students have gotten used to doing various activities with the basic concepts of multiliteracy. Multiliteracy based on character education has been implemented through character values in the implementation of the school literacy movement. How to improve literacy skills of elementary school students, namely growing awareness of the importance of reading; read 15 minutes before teaching and learning activities (KBM); optimize the role of the library; and make simple writings; and form a reading community. Multiliteracy program with school literacy ability activities to positively shape character and uphold the character values of students so that this conceptual study contributes to improving student literacy.